THE CHARATERISTICS OF TEMPOYAK POWDER AS A CONDIMENT IN VARIOUS THE DRYING TEMPERATURES AND OF MALTODEXTRINS - Susi Novianti; Sulvi Purwayantie; Sholah Uddin (Fakultas Pertanian Universitas Tanjungpura, 2019)
Tempoyak was a processed product of durian fermentation spontaneously by lactid acid bacteria (BAL). The objective of this research was to know the effect of drying temperatures and addition of maltodextrins to characteristics condiment of tempoyak powder. This research was used factorial randomized block design (RBD) with two factors. The first factor was concentration maltodextrin (5 and 10%) and the second factor was drying temperature (40, 50 and 60ºC). The data was analyzed by ANOVA 5% if the effect was continued by the test Tukey 5%. The results showed there is no interaction between drying temperature and addition of maltodextrin on total acid, water absorption while the drying time occurs interaction. The treatment of maltodextrin was significant different for total acid, water absorption, and drying time while the drying temperature which was significant different was only drying time. The hedonic test of aroma attribute was different not real. The best treatment by descriptive was result by addition concentration maltodextrin 10% and drying temperature 60°C, with total acid 0.54%, water absorption 9.76%, 8,02 hours of drying time and hedonic value aroma attribute 5( like).Keyword: tempoyak, condiment, drying, maltodextrin